Phytochemistry, and pharmacological efficacy of Cordia dichotoma G. Forst. (Lashuda): A therapeutic medicinal plant of Himachal Pradesh - Raghuvanshi, Disha; Sharma, Kiran; Verma, Rachna; Kumar, Dinesh; Kumar, Harsh; Khan, Azhar; Valko, Marian; Alomar, Suliman Y; Alwasel, Saleh H; Nepovimova, Eugenie; Kuca, Kamil (Biomedicine & pharmacotherapy, 2022)
Cordia dichotoma, Indian cherry is one of the traditional medicinal plant well-known for its medicinal properties against variety of diseases primarily hepatocellular disorders. C. dichotoma is moderate size tree that may be found throughout the Himachal Pradesh and commonly called as lashuda. The objective of the present study is to emphasize the phytochemical and pharmacological study with hepatocurative assessment of C. dichotoma to strengthen not only traditional knowledge but also to validate scientific value of its medicinal potential. Furthermore, comprehensive literature information of C. dichotoma has been compiled from the variety of sources, including scientific databases like PubMed and Google Scholar and pertinent publications and books. The information provided in this study covers the years from 1956 to 2021 and KingDraw chemical structure editor software was used to depict the chemical structures of various secondary metabolites such as flavonoids, tannins, alkaloids, proteins carbohydrate and phenolic compounds extracted from the different parts of the C. dichotoma. Although, flavonoids and phenolic compounds are the most prominent phytoconstituents predominantly detected in C. dichotoma, which are known for great antioxidant potential and also they are renowned for their various pharmacological and therapeutic efficiency against various chronic diseases. Overall, the studies included in this review implies that the plant and its extracts have significant therapeutic benefits not only for hepatic but also for a variety of diseases. While further research is required to fully understand the processes underlying C. dichotoma application in various pharmacological activities.
Keywords: Hepatoprotection; flavonoidy; fytonutrienty; Phytoconstituent; Cordia; fenoly; rostlinné extrakty; Flavonoids; Phenols; Hepatitis; Biochemical parameters; léčivé rostliny; Oxidative stress; fytoterapie; Plant Extracts; Phytochemicals; Plants, Medicinal; Pharmacological activities; Phytotherapy